The Application of Self Organized Learning Environment (SOLE) Learning Model on Learning Outcomes of German Language Teaching Planning Course - Marantika, Juliaans E. R.; Wenno, Eldaa Crystle; Tomasouw, Jolanda (Pattimura Excellence Journal of Language and Culture, 2022)
The implementation of Distance Learning (PJJ), carried out at the German Language Education Study Program at Pattimura University, is inseparable from various obstacles that hinder the lecture process, one of which is the learning outcomes obtained by students. This study is quasi-experimental quantitative research, namely One-Group Pretest-Posttest, to test the effect of the application of the Self Organized Learning Environment (SOLE) learning model on student learning outcomes in the German Language Teaching Planning Course. The sample consisted of 30 5th-semester students of the German Language Education Study Program. The instrument used in this study was tests. The results of the data analysis showed that the students’ posttest was higher than the pretest, with an average score (mean) of the pretest = 74.93 and an average score (mean) of the posttest = 89.86. This result means that there is an influence in the application of the SOLE model on the students’ learning outcomes.